PENGARUH KONSUMSI IKAN YANG TERKONTAMINASI MIKROPLASTIK TERHADAP KESEHATAN TUBUH - Nisa, Zahra; Rakhmawati, Indah; Bashri, Ahmad (Universitas Ahmad Dahlan, 2023)
Plastic waste is a problem that must be addressed immediately. The existence of plastic waste is increasing along with the increase in the human population. Plastic waste that is just thrown away will not decompose, but will only shrink into smaller ones through physical or chemical processes. Plastics that shrink into smaller ones are called microplastics and have a size of <1-5 m. Microplastics scattered in the ocean can be accidentally consumed by fish or another marine biota. This is because the size of the microplastics is very small and very similar to their natural prey. As a result, fish and another marine biota mistakenly identify microplastics as prey. This study was conducted to analyze the effect of consuming fish contaminated with microplastics on the health of the human body. This study uses a literature review method, in which literature such as articles published in accredited journals, books, and websites are relevant to the issues to be discussed. Based on the research, it was found that some water and fish in Indonesia have been contaminated by microplastics. Microplastics that enter the human body and other living things cause adverse effects. In humans, microplastics can enter vital organs. Whereas in other living things, especially fish, microplastics can interfere with the digestive system and can even cause death in fish. Therefore, it is necessary to take action to reduce and control the use of plastic.